Political Communication of the General Election Commission (KPU) of East Luwu Regency in Increasing the Participation of Disabled Voters in the 2020 Regional Elections - Hamdan, Hamdan; Muhammad, Firdaus; Djalil , Nur Alim (Journal of Management and Administration Provision, 2023)
The study aims to analyse the political communication strategies employed by the General Election Commission (KPU) of East Luwu Regency in increasing the participation of voters with disabilities during the 2020 Regional Head Elections. This qualitative research uses descriptive methods, focusing on how political communication impacts the participation of disabled voters. Data were collected through interviews, observation, and literature review, involving KPU officials and disabled voters. The results showed that KPU's communication strategies, such as targeted socialization and partnerships with disability organizations, significantly influenced voter participation. However, barriers such as limited accessibility and lack of family support hindered full voter engagement. The conclusion suggests that improving infrastructure and increasing awareness among families and communities are crucial to enhancing the political participation of voters with disabilities.